DICTION AND FIGURATIVE LANGUAGE IN DRAMA "WATASHITACHI WA DOUKA SHITEIRU" BY NATSUMI ANDO - Pratita, Ina Ika; Parastuti, Parastuti; Ula, Della Mauladul (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2024)
The purpose of this study is to describe and explain the diction and figurative language contained in the drama Watashitachi wa Douka Shiteiru by Natsumi Ando. This research employed the descriptive qualitative method. As for the data provision techniques, the authors used observation and note-taking techniques. Then, the authors analyzed the findings using the translational equivalent method and descriptively presented the results. The research results showed that: a. The uniqueness of the use of language in the drama Watashitachi wa Douka Shiteiru can be seen in the diction, which refers to the meaning of the use of certain words that the author deliberately chose as follows: (1) diction related to the use of typical greetings, (2) diction related to 「外国語」"gairaigo," (3) diction related to the job of making traditional cakes, and (4) diction related to the use of the word connotations The figurative language typesused in the drama Watashitachi wa Douka Shiteiru include simile, metaphor, metonymy, synecdoche, and personification. This research is essential as a reference for Japanese language learners, teachers, and researchersto understand the Japanese language and culture.